PENDUGAAN MODEL PERAMALAN HARGA EKSPOR KOPI INDONESIA - FAUZI EMLAN; Wawan Eka Putra; Andi Ishak; Herlena Bidi Astuti (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
ABSTRACT This study aims to examine the best forecasting model for the export price of Indonesian coffee. The data used in this study are monthly data on coffee prices from January 2012 to September 2019. Three price forecasting models used are moving average, single exponential smoothing and trend analysis are applied to determine the best model based on the lowest MAPE, MAD, and MSE values. The results showed the best model for forecasting the export price of coffee is the moving average (MA1) model because it has the smallest MAPE, MAD and MSE values ​​compared to other models. Keywords: Price, Coffee, Forecasting, Export